Endoscopic ultrasound‐guided hepaticogastrostomy for intraductal papillary neoplasm of bile duct with obstructive jaundice and cholangitis due to mucus overproduction. Issue 4 (14th April 2020) - Hinokuchi, Makoto; Iwaya, Hiromichi; Ido, Akio
Abstract : Watch a video of this article